INTERDISCIPLINARY RISK ANALYSIS: ENSURING THE RELIABILITY OF THE POWER SYSTEM WITH HIGH RESEARCH AND DEVELOPMENT INFILTRATION THROUGH A RAPID RESPONSE METHODOLOGY - Ткачук, Іван (SWorldJournal, 2026)
The sustainability of the energy sector requires the implementation of a synergistic comprehensive approach that combines the implementation of technological innovations, effective management and a risk management system. Against the background of the int